Penerapan Metode Forward Chaining untuk Sistem Pakar Diagnosis Penyakit Ginjal Berbasis Website - Husaini; At-Tharfi’in, Khairunnisa; Misbullah, Alim; Zahnur (Jurusan Sistem Informasi Fakultas Ilmu Komputer Universitas Sriwijaya, 2025)
An expert system is used to replicate the knowledge and reasoning of an expert to assist in decision-making, diagnosis, prediction, and problem-solving in a specific field. Expert systems have been applied across various domains, including healthcare, such as for diagnosing kidney diseases. In this case, the web-based expert system for kidney disease diagnosis is designed to help analyze symptoms and provide an initial diagnosis based on the knowledge and rules of an expert. The system is designed to be utilized by the public, allowing users to input their symptoms, after which the system will provide a diagnosis. It is expected that this expert system can help the public detect kidney disorders early by applying expert knowledge integrated within the system. Another benefit of this system is that it makes it easier for users to perform self-diagnosis and detect potential kidney issues early based on the symptoms they experience. This expert system is developed using the forward chaining method, leveraging the Laravel framework and MySQL database. Forward chaining is a reasoning technique that starts by using available facts and then progresses through relevant premises to reach a conclusion. The use of this method ensures a systematic and accurate reasoning process for generating diagnoses or decisions based on the input information. Testing of the application shows that the developed expert system has successfully met expectations in helping the public accurately and easily identify kidney diseases. Additionally, the application of forward chaining allows the system to provide precise diagnoses based on the symptoms entered by the user, improving the ease of access to health information efficiently.